Using Information Search Strategy to Reconstruct Students' Biology Prior Knowledge - Wakhidah, Nur; Erman, Erman (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to determine changes in students' prior knowledge of preconception reconstruction results using information-seeking strategies in learning. A total of 26 student-teacher candidates at an Islamic university in Surabaya, East Java, were involved voluntarily in this survey research. At the beginning of the lecture, students take part in the pre-test, learning using information searching strategies for seven weeks, and post-test at the end of the lecture. Data analysis was performed using content analysis and t-test understanding analysis to determine changes in student preconceptions. The results showed that there were very significant differences in students' understanding of science due to conceptual changes after learning using information searching strategies. The percentage of students who maintained correct preconceptions was greater than those with incorrect preconceptions. That is what changes the preconception from false to true. The implication is that information searching can help students make decisions to maintain or change their preconceptions.